2002
DOI: 10.1038/ng1044
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in two adjacent novel genes are associated with epidermodysplasia verruciformis

Abstract: Epidermodysplasia verruciformis (OMIM 226400) is a rare autosomal recessive genodermatosis associated with a high risk of skin carcinoma that results from an abnormal susceptibility to infection by specific human papillomaviruses (HPVs). We recently mapped a susceptibility locus for epidermodysplasia verruciformis (EV1) to chromosome 17q25. Here we report the identification of nonsense mutations in two adjacent novel genes, EVER1 and EVER2, that are associated with the disease. The gene products EVER1 and EVER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
303
1
11

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 391 publications
(320 citation statements)
references
References 10 publications
5
303
1
11
Order By: Relevance
“…2 Genome-wide linkage studies were performed to map two EV loci 3,4 and to identify the EVER genes (EVER1 or EVER2, also referred to as TMC6 and TMC8, respectively) in one of these loci. 5 The identification of EVER1 and EVER2 expressed sequence tags and cDNA from lymphoid tissue is consistent with a model in which EV mutations exert their direct effects in the immune system. It was recently discovered that 75% of EV patients studied have rare mutations in either of these adjacent, related, novel genes.…”
mentioning
confidence: 59%
“…2 Genome-wide linkage studies were performed to map two EV loci 3,4 and to identify the EVER genes (EVER1 or EVER2, also referred to as TMC6 and TMC8, respectively) in one of these loci. 5 The identification of EVER1 and EVER2 expressed sequence tags and cDNA from lymphoid tissue is consistent with a model in which EV mutations exert their direct effects in the immune system. It was recently discovered that 75% of EV patients studied have rare mutations in either of these adjacent, related, novel genes.…”
mentioning
confidence: 59%
“…One is that antibodies are a good marker of pathogenic skin infection, and variation in susceptibility to infection might therefore underpin the clustering. There are two main genes that are thought to determine such susceptibility, the EVER1 and EVER2 genes, which are mutated in patients with EV (Ramoz et al, 2002). A recent study showed that controls in a case-control study who carried a particular single-nucleotide polymorphism in the EVER2 gene were more likely to carry bPV antibodies and had a greater likelihood of having antibodies to multiple viruses (Patel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in EVER1 and EVER2 genes result in susceptibility to beta-human papillomavirus (β-HPV) infection and a high risk of skin cancer -about 50% of the patients eventually develop cSCC (Ramoz et al, 2002). Onset of lesions usually appears within the first decade, with cSCCs appearing at an average age of 20 at sun-exposed areas (de Oliveira et al, 2003;Gul et al, 2007).…”
Section: Epidermodysplasia Verruciformismentioning
confidence: 99%